The Probability of Extra-Constitutional Amendment on the 1945 Constitution of Indonesia: The Politic of Parliament Against its Constitutionalism - Syanel, Muhammad Faiz Putra; Haq, Zul Amirul; Putra, Muhamad Aljabar (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Is the constitution a 'product' of Parliament, or is it run its constitutionalism? This question directs the attention of this article to the distinction between glorification and constitutional amendment. The constitution has an unamendable provision that serves as a self-limitation. This restriction is enshrined in constitutional conventions, and it emphasizes that the Parliament cannot rewrite the constitution in a way that abolished the natural character of the constitution. The Parliament, on the other hand, is the organ of government. This body was given the power to amend the Constitution by the Constitution. As a result, it designates Parliament as the greater authority in charge of all organs as well as the constitution. The research of its article uses philosophy and comparative methodology. It took a doctrinal approach to determine the correlation between political will and constitutional normativity while the amendment was in place. The political wills of Parliament are essentially determined by the normativity of the constitution, as the Parliament was born from a constitutional norm. Whereas, according to Hans Kelsen, the constitution existed before all the norms. In this paradox, the constitution was born before the Parliament itself.Keywords: Constitution; Constitutionalism; Natural Character Unamendable Provision, Parliament AbstrakApakah konstitusi merupakan produk dari Parlemen, atau konstitusi menjalankan konstitusionalismenya? Pertanyaan memantik atensi dari tulisan ini yang berfokus pada distingsi antara glorifikasi konstitusi dan proses amandemen. Secara faktual, konstitusi memiliki klausula yang tidak dapat diubah sebagai batasan perubahannya. Limitasi tersebut memiliki fokus pada konvensi konstitusional, dan menegaskan bahwa Parlemen tidak dapat mengubah konstitusi hingga merubah ‘karakter awal’ dari konstitusi itu sendiri. Meskipun Parlemen merupakan Lembaga Pemerintahan, kewenangannya untuk dapat merubah konstitusi pada dasarnya diberikan oleh Konstitusi. Konsekuensinya, Parlemen terdesain secara tidak langsung sebagai lembaga tertinggi yang dimandatkan oleh konstitusi. Untuk mengelaborasi permasalahan tersebut, penelitian ini menggunakan metode filosofi dan komparasi hokum. Dengan pendekatan Filsafat, akan didapatkan pandangan atas determinasi hubungan antara kehendak politik dengan normatifitas konstitusi pada saat amandemen sedang berlangsung.  Secara Ideal, kehendak politik parlemen terdeterminasi oleh normatifitas konstitusi, karena parlemen dilahirkan dari Rahim konstitusi. Sedangkan, menurut Hans Kelsen, konstitusi telah lahir jauh sebelum seluruh norma. Dalam paradoks ini, disimpulkan bahwa konstitusi telah lahir jauh sebelum parlemen.Keywords: Konstitusi; Konstitusionalisme; Karakter Konstitusi; Klausula yang Tidak Dapat Diubah; Parlemen